2019
DOI: 10.1111/ctr.13612
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cardiac autonomic response in lung transplant patients: A retrospective cohort study

Abstract: Background Cardiac autonomic dysfunction (AD) is associated with adverse prognosis in lung disease; however, its implications in lung transplantation have not been previously described. This study evaluated the prevalence of AD in lung transplant (LTx) candidates, its determinants, prognostic implications, and prevalence post‐transplant. Methods Retrospective one‐year study of 103 LTx candidates with AD assessed using heart rate (HR) from the six‐minute walk test (6MWT). Impaired chronotropic response index (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Heart rate (HR) response, peak aerobic capacity, oxygen pulse (measure of cardiac stroke volume), and minute ventilation (product of tidal volume and respiratory rate) will be collected throughout the exercise and up to 2 minutes after test completion with unloaded pedaling, with percent predicted values reported. HR recovery (difference between peak HR and HR 1 minute after exercise) and the chronotropic response index ([peak HR – resting HR × 100] / [220 – age] – [resting HR]) will be collected as a measure of autonomic function [ 51 - 53 ]. Chronotropic incompetence is the inability to decrease HR after exercise or the inability to reach 80% of the maximal age-predicted HR because of abnormal sympathetic activation [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heart rate (HR) response, peak aerobic capacity, oxygen pulse (measure of cardiac stroke volume), and minute ventilation (product of tidal volume and respiratory rate) will be collected throughout the exercise and up to 2 minutes after test completion with unloaded pedaling, with percent predicted values reported. HR recovery (difference between peak HR and HR 1 minute after exercise) and the chronotropic response index ([peak HR – resting HR × 100] / [220 – age] – [resting HR]) will be collected as a measure of autonomic function [ 51 - 53 ]. Chronotropic incompetence is the inability to decrease HR after exercise or the inability to reach 80% of the maximal age-predicted HR because of abnormal sympathetic activation [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…HR recovery (difference between peak HR and HR 1 minute after exercise) and the chronotropic response index ([peak HR – resting HR × 100] / [220 – age] – [resting HR]) will be collected as a measure of autonomic function [ 51 - 53 ]. Chronotropic incompetence is the inability to decrease HR after exercise or the inability to reach 80% of the maximal age-predicted HR because of abnormal sympathetic activation [ 51 ]. Symptom intensity for breathing and leg discomfort with exercise will be measured at rest and every 3 minutes throughout the exercise using the Borg dyspnea [ 54 ] and leg fatigue scales [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis found that pretransplant depression predicted posttransplant depression and increased risk of posttransplant mortality, with depression being determined with diagnostic assessments or standardized symptoms scales (Dew et al, 2015). This effect is hypothesized in part to be through behavioral pathways, including depression contributing to poorer medical adherence (Cukor et al, 2009;Delibasic et al, 2017), reduced physical activity (Dew et al, 2018;Kop et al, 2011), substance abuse (Kop, 2010), and potential dysregulation in neurohormones, autonomic nervous system function, or inflammatory processes (Kop et al, 2011;Martelli et al, 2019). These biobehavioral processes may pose an increased risk for infections, complications, rehospitalization, graft rejection, and/or mortality (Dew et al, 2018).…”
Section: Depression and Anxietymentioning
confidence: 99%
“…reduced exercise capacity and physical function limitations are multifactorial, including alterations in lung mechanics and gas exchange, cardiovascular limitations, peripheral muscle dysfunction, deconditioning, malnutrition, fatigue, and anemia. [5][6][7][8][9][10] Improvements posttransplant in physical capacity are observed mainly because of improved organ function and reduction of disease symptoms. 7 However, exercise capacity is still impaired in transplant recipients with 40% to 70% of age-predicted values.…”
Section: Reviewmentioning
confidence: 99%